2022
DOI: 10.3389/fpls.2022.805633
|View full text |Cite
|
Sign up to set email alerts
|

Arabidopsis Tetraspanins Facilitate Virus Infection via Membrane-Recognition GCCK/RP Motif and Cysteine Residues

Abstract: Tetraspanins (TETs) function as key molecular scaffolds for surface signal recognition and transduction via the assembly of tetraspanin-enriched microdomains. TETs’ function in mammalian has been intensively investigated for the organization of multimolecular membrane complexes, regulation of cell migration and cellular adhesion, whereas plant TET studies lag far behind. Animal and plant TETs share similar topologies, despite the hallmark of “CCG” in the large extracellular loop of animal TETs, plant TETs cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 84 publications
(119 reference statements)
0
10
0
Order By: Relevance
“…Tetraspanins have been shown to be heavily involved in animal virus infection, with roles in virus entry/endocytosis, trafficking, and budding of enveloped viruses ( Florin and Lang, 2018 ). It was recently shown that tetraspanin 3 proteins also play an important role in enhancing plant virus cell-to-cell movement and infection in A. thaliana ( Zhu et al, 2022 ). LTPs are responsible for non-vesicular trafficking of lipids in cells.…”
Section: Resultsmentioning
confidence: 99%
“…Tetraspanins have been shown to be heavily involved in animal virus infection, with roles in virus entry/endocytosis, trafficking, and budding of enveloped viruses ( Florin and Lang, 2018 ). It was recently shown that tetraspanin 3 proteins also play an important role in enhancing plant virus cell-to-cell movement and infection in A. thaliana ( Zhu et al, 2022 ). LTPs are responsible for non-vesicular trafficking of lipids in cells.…”
Section: Resultsmentioning
confidence: 99%
“…More than 33 Tspans, such as Tspan7 , span9 , CD9 , CD81 , and CD151 , are known to be involved in the process of virus infestation in human cells [ 33 ]. Tetraspanins in A. thaliana facilitate CMV infection through specific membrane-recognition motifs [ 34 ]. However, in our study Tspan (Tetraspanin-20) displayed stable expression in N. benthamiana plants infected by ToMMV, ChiRSV, ChiVMV or PVX, suggesting that Tspan plays no significant role in infection by these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…This result confirmed that fluorescent C-terminal, as well as N-terminal, TET1 fusions are not functional. This necessitates careful re-evaluation of any data involving such reporters, as well as well as fluorescent fusions of other TET homologues whose functionality had not been tested (Yamaguchi et al, 2017; Zhu et al, 2022). Overall, we hope that our work demonstrates the importance of generating full knock out mutant lines and checking for full complementation before continuing any sort of in-depth analysis of generated material, as well as providing a solid foundation for further work on TET proteins in root development.…”
Section: Discussionmentioning
confidence: 99%
“…Scaffolding and partitioning of various multiprotein complexes into the so-called TETRASPANIN-Enriched Microdomains (TEMs) at the plasma membrane (PM) is a recurrent mode of TET action across their diverse functional roles (Reimann et al, 2017). Comparatively, less is characterized when it comes to the function and localization of TETs in plants, although it has been shown that their PM localization depends on the presence of a “GCCK/RP” motifs and cysteine residues (Zhu et al, 2022). Most single mutants show no striking phenotypes, suggesting a high degree of functional redundancy in the family (Wang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%